2022
DOI: 10.1007/s10278-022-00705-9
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion SPECT Imaging Radiomic Features and Machine Learning Algorithms for Cardiac Contractile Pattern Recognition

Abstract: A U-shaped contraction pattern was shown to be associated with a better Cardiac resynchronization therapy (CRT) response. The main goal of this study is to automatically recognize left ventricular contractile patterns using machine learning algorithms trained on conventional quantitative features (ConQuaFea) and radiomic features extracted from Gated single-photon emission computed tomography myocardial perfusion imaging (GSPECT MPI). Among 98 patients with standard resting GSPECT MPI included in this study, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In this light, the term "radiomics" can be put forward as it fundamentally describes the analysis of medical images via computational data extraction and, in other words, transforming images into minable biomarkers [9][10][11]. Radiomics can help us prepare data hidden in images that cannot be seen with conventional image assessment methods with the naked eye in different diseases [12][13][14][15][16]. Whether in the diagnostic or the prognostic area, cancer research has always been of interest to radiomics researchers, and GBM is not an exception [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this light, the term "radiomics" can be put forward as it fundamentally describes the analysis of medical images via computational data extraction and, in other words, transforming images into minable biomarkers [9][10][11]. Radiomics can help us prepare data hidden in images that cannot be seen with conventional image assessment methods with the naked eye in different diseases [12][13][14][15][16]. Whether in the diagnostic or the prognostic area, cancer research has always been of interest to radiomics researchers, and GBM is not an exception [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the variability of features over different imaging settings is feature-dependent and identified robust radiomics features for further studies. Sabouri et al 34 , 35 studied to identify left ventricle contractile patterns using conventional quantitative and radiomic features extracted from MPI-SPECT and machine learning algorithms. Their proposed model achieved promising results for detecting left ventricle contractile patterns, which can further be used for cardiac resynchronization therapy response prediction.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Additionally, there are few radiomics studies on SPECT/CT, most of which are based on myocardial or lung perfusion imaging, and studies on bone imaging are rare. [24][25][26][27] There was study showed that doctors still have ambiguous diagnoses regarding the results for 14.3% of patients after undergoing 99m Tc-MDP SPECT/CT examination. 28 Therefore, it is necessary to develop a machine learning approach with SPECT/CT to differentiate between bone metastases and benign bone lesions in patients with lung cancer, with the intention of assisting clinicians in making more accurate clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, most current studies on radiomics in bone metastasis of lung cancer only considers the diagnostic value of radiomics features or clinical features without investigating their added value 22,23 . Additionally, there are few radiomics studies on SPECT/CT, most of which are based on myocardial or lung perfusion imaging, and studies on bone imaging are rare 24–27 . There was study showed that doctors still have ambiguous diagnoses regarding the results for 14.3% of patients after undergoing 99m Tc‐MDP SPECT/CT examination 28 .…”
Section: Introductionmentioning
confidence: 99%